BACKGROUND CONCENTRATION OF MICROELEMENTS IN ULAANBAATAR REGIONAL NATURAL SURFACE SOIL - Ts, Byambasuren; B, Khuukhenkhuu; G, Ochirbat; E, Vasilyeva I; V, Shabanova E; D, Tsedenbaljir; T, Korolkov A (Proceedings of the Mongolian Academy of Sciences, 2018)
In this paper were presented the background values in total content and bioavailable concentration of trace elements in regional surface soil of Ulaanbaatar city. The main goal of this study is to establish the total content and bio-available concentration of microelements in natural soil of around Ulaanbaatar and to standardize them as main criterion in assessment of soil pollution by heavy metals. Background sites were selected in 20-40 km from the city center and in the resident zone. In soil samples using the complex analytical methods of atomic spectroscopy have been determined the total content and bio-available concentration of microelements.